Analisis Preferensi Ketidaknyamanan Konsumen Terhadap Promosi Dan Personal Selleryang Mempengaruhi Minat Beli Konsumen Serta Pemilihan Merek Pada Asuransi (Studi Kasus di PT. Prudential Life Assurance) - Putu Dyah Permatha Korry; Ayu Wendy Widhia Pramesti (Universitas Mahendradatta Denpasar, 2019)
Health is an important thing to be noticed in everyday life, because humans will not be separated from the dangers that arise suddenly by an event. Insurance is one way to guarantee a sense of security in handling the risks that arise suddenly. No wonder various promotions are carried out by companies to generate consumer buying interest, but one of the promotional techniques of direct marketing through telemarketing is inconvenience, because promotion through this technique consumers feel disturbed when contacted because according to them telemarketers do not think of the right time when offering a product. Personal Sales (Personal Seller) is an insurance agent from a company that can deal directly with consumers so that later there will be buying interest in insurance. To increase consumer buying interest, promotional inconvenience, and seller personalities are expected to be able to influence consumers so that after buying interest arises, consumers will be able to decide on the brand selection on insurance. Data was collected through questionnaires to 85 respondents. The data analysis technique used is structural equation (SEM) with PLS. The results of this study indicate that promotional discomfort has a negative and significant effect on consumer buying interest, while a personal seller has a positive and significant effect on consumer buying interest, and consumer buying interest has a positive and significant effect on brand selection. Based on the results of testing the Q2 model gets a value of 0.774, which shows the predicted model is appropriate.